Validity and reliability of the Chinese version of the Daily Living Self-Efficacy Scale among stroke patients. Issue 3 (September 2016) - Li, Hong-Yan; Cheng, Hui-Lin; Fang, Liang; Bi, Rui-Xue; Fang, Xiao-Qun; Hu, Min
Abstract : The aim of this study was to examine the reliability and validity of the Chinese version of the Daily Living Self-Efficacy Scale (DLSES) in stroke patients. In total, 172 participants were recruited from a local hospital in China. The internal consistent reliability and convergent validity of the total scale and activities of daily living (ADL) and psychosocial functioning subscales were examined and factor analysis was carried out. Cronbach's α s for the Chinese version of the DLSES, ADL subscale, and psychosocial subscale were 0.96, 0.90, and 0.95, respectively. In the factor analysis, two factors (ADL and psychosocial functioning) were extracted, explaining 84.4% of the total variance in self-efficacy ( χ 2 /d.f. =2.19, root mean square error of approximation=0.08, normed fit index=0.95, comparative fit index=0.98, incremental fit index=0.98). Convergent validity was confirmed by positive relationships between the Chinese version of the DLSES and the Modified Fall Efficacy Scale ( r =0.87). The ADL subscale was associated positively with the Barthel Index ( r =0.74) and the psychosocial functioning subscale was associated negatively with the Functional Activities Questionnaire ( r =−0.73) and Center for Epidemiologic Studies Depression Scale ( r =−0.44). The Chinese version of the DLSES was shown to be a reliable and valid measure of self-efficacy in stroke patients.